2022
DOI: 10.24251/hicss.2022.582
|View full text |Cite
|
Sign up to set email alerts
|

What do Users Actually Look at During ‘Zoom’ Meetings? Discovery Research on Attention, Gender and Distraction Effects

Abstract: During the pandemic, mandatory shutdowns of schools and businesses forced people to communicate almost exclusively through computer-based video communications tools. The transition brought challenges, as users adjusted to the new environment, wading through various distractions, all the while learning the technology on the go. The existing research into Zoom meetings says little about what users actually observe during these meetings. This discovery-based study explores what users attend to in remote meetings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In addition, Fauville et al (2021) empirically examined videoconference fatigue and found a gender gap: women were found to be impacted more by the self-view effect. Further evidence was provided by an eye-tracking study that confirmed women looked more at themselves than men (George et al, 2022). In addition to the gender gap, Shockley et al (2021) found a more severe effect on fatigue of camera usage for employees with less tenure in the organization.…”
Section: The Covid-19 Pandemic and Wellbeingmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, Fauville et al (2021) empirically examined videoconference fatigue and found a gender gap: women were found to be impacted more by the self-view effect. Further evidence was provided by an eye-tracking study that confirmed women looked more at themselves than men (George et al, 2022). In addition to the gender gap, Shockley et al (2021) found a more severe effect on fatigue of camera usage for employees with less tenure in the organization.…”
Section: The Covid-19 Pandemic and Wellbeingmentioning
confidence: 94%
“…(2021) empirically examined videoconference fatigue and found a gender gap: women were found to be impacted more by the self-view effect. Further evidence was provided by an eye-tracking study that confirmed women looked more at themselves than men (George et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…There are elements of social presence and perception of a virtual fidget that could be investigated, such as an indicator when a student is using a virtual fidget to avoid misunderstandings or incorrect assumptions [26]. This would also reduce the virtual fidget user's stress of monitoring self-presentation [14]. Alternatively, instructors might see virtual fidgets as an opportunity to engage students in a new way, and future work could develop fidgets that are responsive and relevant to their specific lecture content.…”
Section: Future Workmentioning
confidence: 99%
“…Understanding students' attention in the presence of multitasking is challenging, as a student might get involved with such activities for a significant duration during a live class [12]. Apart from that, gazing at the screen is not an essential condition for getting involved in an online meeting [19,20]. As shown in several recent studies, a student might still get actively involved in a virtual classroom even if they minimally gaze at the screen [9,16,18,42].…”
Section: Introductionmentioning
confidence: 99%